Clidocraneal dysostosis: Literature review and report of a clinical case. - Bernardita Toro; Antonieta Pérez; Claudia Fierro (Universidad de Concepción., 2012)
Cleidocranial dysostosis (CCD) is a rare congenital skeletal disorder associated to clavicular hypoplasia or aplasia, delayed closure of fontanelles head with brachycephalic type, delayed exfoliation of primary teeth, delayed eruption of permanent teeth, presence of several supernumeraries and morphological changes on the maxilla and mandible. This disorder is inherited as an autosomal dominant condition and 40% of the cases appear spontaneously without apparent genetic cause. Early diagnosis is very important to give patients the best treatment options. In this article, literature regarding CCD, its etiology, early diagnosis, and general and dental features. A patient with this condition is presented.